The Influence of The Principal's Managerial Ability and Teacher Work Culture on Teacher Performance State Vocational Schools - Melati Raya Pasaribu; Andar G. Pasaribu; Betty A.S. Pakpahan (Jurnal Ilmu Pendidikan dan Sosial, 2026)
This study aims to determine the number and analyze the influence 1) the principal's managerial ability on the performance of state vocational high school teachers in Doloksanggul District; 2) the teacher work culture on the performance of state vocational high school teachers in Doloksanggul District; and 3) the principal's managerial ability and teacher work culture on the performance of state vocational high school teachers in Doloksanggul District. This study used a quantitative method with an ex post facto or survey type. The population was all 158 teachers in state vocational high schools in Doloksanggul District. Using the Slovin formula with a 5% margin of error, a sample of 115 teachers was taken. Data were collected using a closed questionnaire consisting of 25 statement items for variable X1 (Principal's Managerial Ability) and 30 statement items for variable X2 (Teacher Work Culture) and 35 statement items to measure variable Y (Teacher Performance), resulting in a total of 90 statement items. Before being used on actual respondents, the instrument was first tested on 30 teachers at SMK Negeri 1 Lintong Nihuta outside the sample. The results of the instrument trial showed that all questionnaire items were valid and reliable. The data analysis technique was carried out using descriptive analysis, variable categorization and parametric statistical analysis with simple and multiple linear regression equation tests, coefficient of determination tests. The results of the data analysis showed that: 1) The Principal's Managerial Ability had a positive and significant effect on Teacher Performance in 2026 of 32.3% and a strong correlation value of 0.568 with the regression equation Y = 69.752 + 0.699X1 and the significant value of the t-test was 0.001 <α = 0.05, and tcount = 7.337> ttable (n-2 = 113) = 1,980. 2) Teacher Work Culture has a positive and significant effect on Teacher Performance in 2026 of 36% and a strong correlation value of 0.601 with the regression equation Y = 73.761 + 0.536X2 and the significant value of the t-test is 0.001 <α = 0.05, and tcount = 7.990> ttable (n-2 = 113) = 1.980 and 3) Principal Managerial Ability and Teacher Work Culture have a positive and significant effect on Teacher Performance together in 2026 of 50% and a strong correlation value of 0.707 with the regression equation Y = 42.330 + 0.493X1 + 0.404X2 and the significant value of the F-test is 0.001 <α = 0.05, and Fcount = 7.337> Ftable (k-1, nk; 2113) = 3.08. Thus, it is concluded that the research hypothesis is accepted.